Influence of creamer addition on chlorogenic acid bioaccessibility and antioxidant activity of instant coffee during in vitro digestion. (November 2021) - Yu, Hyunjong; Jeon, Hyejoo; Myeong, Jaeho; Kwon, Chang Woo; Chang, Pahn-Shick
Abstract: Coffee phenolics are unstable in gastrointestinal tract, but they can be protected during digestion by interaction with milk proteins. The objectives of this study are to evaluate effects of creamers containing milk proteins on the bioaccessibility of chlorogenic acids (CGAs) and antioxidant activity of instant coffee during in vitro digestion. The bioaccessibility of CGAs in instant coffee beverage (IC), instant coffee beverages with creamer A (CRA), with creamer B (CRB), and with skim milk (SM) was 26.4%, 40.5%, 51.7%, and 83.6%, respectively. These results indicated that creamers and skim milk increased the bioaccessibility of CGAs in a manner correlated with protein concentration. After digestion, IC showed the highest decrease (25.6%) in ferric reducing antioxidant power (FRAP), compared to that before digestion; lower decreases were observed in CRA (12.7%), CRB (16.2%), and SM (13.8%). These findings suggest that consumption of instant coffee with creamers helps to retain the biological activity of coffee phenolics during digestion. Graphical abstract: Image 1 Highlights: Creamers increased bioaccessibility of chlorogenic acids (CGAs) in instant coffee. Increases in the bioaccessibility were correlated with protein concentrations. Creamers preserved antioxidant activity of instant coffee during in vitro digestion. The effects of creamer were attributed to complexation of phenolics with proteins.